Short-Term Diet Induced Changes in the Central and Circulating IGF Systems Are Sex Specific - Guerra-Cantera, Santiago; Frago, Laura M.; Díaz, Francisca; Ros, Purificacion; Jiménez-Hernaiz, Maria; Freire-Regatillo, Alejandra; Barrios, Vicente; Argente, Jesús; Chowen, Julie A. (Frontiers in Endocrinology, 2020)
Insulin-like growth factor (IGF) 1 exerts a wide range of functions in mammalians participating not only in the control of growth and metabolism, but also in other actions such as neuroprotection. Nutritional status modifies the IGF system, although little is known regarding how diet affects the newest members of this system including pregnancy-associated plasma protein-A (PAPP-A) and PAPP-A2, proteases that liberate IGF from the IGF-binding proteins (IGFBPs), and stanniocalcins (STCs) that inhibit PAPP-A and PAPP-A2 activity. Here we explored if a one-week dietary change to either a high-fat diet (HFD) or a low-fat diet (LFD) modifies the central and peripheral IGF systems in both male and female Wistar rats. The circulating IGF system showed sex differences in most of its members at baseline. Males had higher levels of both free (p<0.001) and total IGF1 (p<0.001), as well as IGFBP3 (p<0.001), IGFBP5 (p<0.001), and insulin (p<0.01). In contrast, females had higher serum levels of PAPP-A2 (p<0.05) and IGFBP2 (p<0.001). The responses to a short-term dietary change were both diet and sex specific. Circulating levels of IGF2 increased in response to LFD intake in females (p<0.001) and decreased in response to HFD intake in males (p<0.001). In females, LFD intake also decreased circulating IGFBP2 levels (p<0.001). In the hypothalamus LFD intake increased IGF2 (p<0.01) and IGFBP2 mRNA (p<0.001) levels, as well as the expression of NPY (p<0.001) and AgRP (p<0.01), but only in males. In conclusion, short-term LFD intake induced more changes in the peripheral and central IGF system than did short-term HFD intake. Moreover, these changes were sex-specific, with IGF2 and IGFBP2 being more highly affected than the other members of the IGF system. One of the main differences between the commercial LFD employed and the HFD or normal rodent chow is that the LFD has a significantly higher sucrose content, suggesting that this nutrient could be involved in the observed responses.